1993
DOI: 10.1055/s-2008-1045669
|View full text |Cite
|
Sign up to set email alerts
|

Wachstumshemmung intraokularer proliferativer Explantate unter in-vitro-Bedingungen durch Verapamil

Abstract: A larger number of cases would have to be studied to permit more comprehensive conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Verapamil inhibits calcium channels in a nanomolar range (Catterall, Seagar and Takahashi, 1988 ;Richter et al, 1993). Because we did not demonstrate any effects on RPE proliferation and migration at these low concentrations, we focused on the possibility that verapamil may be acting through its known effects on PKC (Mori et al, 1980).…”
Section: Verapamil Reversibly Inhibits Pkc Activitymentioning
confidence: 98%
See 1 more Smart Citation
“…Verapamil inhibits calcium channels in a nanomolar range (Catterall, Seagar and Takahashi, 1988 ;Richter et al, 1993). Because we did not demonstrate any effects on RPE proliferation and migration at these low concentrations, we focused on the possibility that verapamil may be acting through its known effects on PKC (Mori et al, 1980).…”
Section: Verapamil Reversibly Inhibits Pkc Activitymentioning
confidence: 98%
“…Verapamil has been shown to inhibit the formation of postsurgical peritoneal adhesions in rabbits (Steinleitner et al, 1990), while in vitro studies have shown that calcium channel blockers inhibit the proliferation of epi-, suband preretinal membranes (Richter, Hatvani and To! th, 1993), as well as the proliferation of tumor cells (Batra et al, 1991 ;Bertrand et al, 1994 ; 0014-4835\98\070045j08 $30.00\0…”
Section: Introductionmentioning
confidence: 98%